PERANAN PENDAMPING DESA DALAM MEMBANTU PEMERINTAH DESA SEBAGAI FASILITATOR PEMBERDAYAAN MASYARAKAT DI DESA PULAU TONGAH KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI TAHUN 2019-2021 - Mesi Aspiweti Sapitri; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The research method here is a qualitative research method that explains and analyzes human behavior. The purpose of this study is to determine the role of village assistants in assisting village government as facilitators of community empowerment in Pulau Tongah Village, Benai District, Kuantan Singingi Regency and to find out the things that become an obstacle to the role of village assistants in assisting village governments as facilitators of community empowerment. Interview and documentation data collection techniques. The type of research used by the author is descriptive, which conducts research directly to Pulau Tongah Village, Benai District, Kuantan Singingi Regency by using a descriptive survey research type with, interviews, and documentation as a tool to collect data.The results of this study are Village Assistants in Pulau Tongah Village as Assistance Personnel in the Framework of Implementing Village Government here carry out village financial training activities with village officials. This village assistant in Pulau Tongah Village assists the implementation of village development, such as monitoring development to completion, village assistants as village community development participate in controlling and monitoring Community Development in the field of Religion such as religious guidance activities for the youth of Tongah Island village and village assistant activities attending the Maulid Nabi. The fourth is the role of village assistants. As an empowerment of village communities, such as village garden maintenance activities, activities to use unused land to plant horticulture crops. The things that become obstacles for Village Facilitators are the first existence of people who do not participate in carrying out development programs. The second is the length of disbursement of funds so that development programs cannot run smoothly.Keywords: Role, Village Facilitator, Empowerment.